Kontroversi dan Transformasi Model Pembelajaran PAI Berbasis Al-Qur'an di Sekolah Multikultural - Ariyanto, Ahmad Badri Lucky; Muhammad, Zaini (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
This study aims to examine the effectiveness of the Qur'an-based Islamic Religious Education (PAI) learning model in improving students' understanding of religious values in multicultural schools, as well as to identify the challenges faced in its implementation. The focus of this research also involves analyzing the impact of the learning model on students' social attitudes in the context of religious diversity. The research method used is a qualitative approach with a descriptive design, involving data collection techniques in the form of in-depth interviews, observations, and documentation studies. The research was conducted at Al-Falah Multicultural Vocational School, Bandung, with data analysis using thematic analysis techniques and triangulation to ensure the validity of the findings. The results showed that the implementation of the Qur'an-based PAI learning model was effective in improving students' understanding of religious values, despite challenges related to inclusiveness for non-Muslim students. The implementation of this model also contributes to the improvement of tolerance and respect for diversity among students. The implication of this study is that the Qur'an-based learning model can be an effective tool in creating a harmonious and inclusive learning environment, although proper management is needed to overcome the challenges of religious diversity in multicultural schools